Proceedings of the International Conference on Research and Academic Community Services (ICRACOS 2019) 2020
DOI: 10.2991/icracos-19.2020.13
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian Students’ Reading Literacy

Abstract: Reading is supposed to be an activity frequently performed by university students. However, not all students are fond of reading, particularly in the digital era. This study aims to identify students' reading literacy both in their family and their campus and determine whether campus library maximally utilized. Performing as the subjects of this study were 307 students at Atma Jaya Catholic University in Jakarta, Indonesia. The data were collected through google docs, in-depth interviews, and observation. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 7 publications
0
25
0
7
Order By: Relevance
“…Readers can grow their critical thinking through different reading processes, along with interpretation, inference, and text-based insights. However, the data obtained from previous research indicated that Indonesian college students still lack reading literacy for several reasons, such as laziness, insufficient time, poor reading habit, lack of vocabulary and background knowledge, and the use of ineffective reading strategies (Velayati, Muslem, Fitriani, & Samad, 2017;Wijayanti, 2020). Therefore, this current study explored critical reading's role to foster the critical thinking and reading comprehension of Indonesian undergraduate students majoring in Social and Political Sciences.…”
Section: Introductionmentioning
confidence: 95%
“…Readers can grow their critical thinking through different reading processes, along with interpretation, inference, and text-based insights. However, the data obtained from previous research indicated that Indonesian college students still lack reading literacy for several reasons, such as laziness, insufficient time, poor reading habit, lack of vocabulary and background knowledge, and the use of ineffective reading strategies (Velayati, Muslem, Fitriani, & Samad, 2017;Wijayanti, 2020). Therefore, this current study explored critical reading's role to foster the critical thinking and reading comprehension of Indonesian undergraduate students majoring in Social and Political Sciences.…”
Section: Introductionmentioning
confidence: 95%
“…They read only one book for the last two months and spent more time with gadgets than reading. The study concluded that Indonesian students' reading literacy was still unsatisfactory [5].…”
Section: Introductionmentioning
confidence: 98%
“…The more they read, the better their academic achievement and understanding of their reading and writing [9], [10]. Furthermore, literacy is a crucial factor influencing intellectual and emotional development [11], [12] and for a better quality of future human resources [5]. Thus, it is crucial to develop literacy from an early age, which is not only for improving academic achievement but also, more importantly, for intellectual and emotional development to develop a better quality of human resources.…”
Section: Introductionmentioning
confidence: 99%
“…Experts agree that reading literacy is a condition sine quanon (absolute prerequisite) for every human being who wants to make progress (Tahmidaten & Krismanto, 2020). Even reading is still the main indicator of the literacy index, including in Indonesia (Wijayanti, 2020).…”
Section: Introductionmentioning
confidence: 99%